Trade‐Induced Unemployment: The Case of Post‐Apartheid South Africa. (3rd June 2013) - Smet, Koen
Abstract: This paper analyses the link between changes in trade flows and labour demand in post‐apartheid South Africa (1994–2006). Although this is not the first research with regard to this topic, it is one of the few that uses a consistent trade framework. Based on a three‐dimensional Heckscher–Ohlin trade model, a theoretical framework is constructed to analyse this link. Whereas it is impossible to test the theoretical link directly because of data limitations, an indirect econometric test supports the findings of the model. This implies that the combination of increased trade and labour market rigidities was unfavourable for labour opportunities.